2017
DOI: 10.1007/s12187-017-9460-0
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Living Conditions of Young People in Secure Residential Care: Psychometric Properties of the Best Interest of the Child − Self-Report Questionnaire (BIC-S)

Abstract: The Best Interest of the Child − Self-report questionnaire (BIC-S) is designed as a tool to ensure young people in secure residential care have a voice about their living environment. The primary aim of this study was to determine the psychometric properties of the BIC-S. Second, we wanted to map the experiences of young people with their current residential living environment. Therefore, both quantitative and qualitative methods were used to assess the experiences of young people with the BIC-S instrument in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Although these results were not replicated in a study based on Central American CWIs (Groark et al, 2013), the use of an in-depth dimensional measure of the rearing environment has nonetheless provided insights into the quality of these Central American CWIs in comparison with equivalent CWIs in Greece (Vorria et al, 2003). Other studies have focused on children's perceived group climate, defined as the quality of the social and physical environment provision that is sufficient and necessary for physical and mental well-being (e.g., perceived support from staff) (Strijbosch, Van der Helm, Stams, & Wissink, 2016;Ten Brummelaar et al, 2017). Results showed that positively perceived group climate was associated with positive outcomes of the children such as better coping, more empathy, and less aggression (Heynen, van der Helm, Cima, Stams, & Korebrits, 2017;van der Helm, Klapwijk, Stams, & van der Laan, 2009).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Although these results were not replicated in a study based on Central American CWIs (Groark et al, 2013), the use of an in-depth dimensional measure of the rearing environment has nonetheless provided insights into the quality of these Central American CWIs in comparison with equivalent CWIs in Greece (Vorria et al, 2003). Other studies have focused on children's perceived group climate, defined as the quality of the social and physical environment provision that is sufficient and necessary for physical and mental well-being (e.g., perceived support from staff) (Strijbosch, Van der Helm, Stams, & Wissink, 2016;Ten Brummelaar et al, 2017). Results showed that positively perceived group climate was associated with positive outcomes of the children such as better coping, more empathy, and less aggression (Heynen, van der Helm, Cima, Stams, & Korebrits, 2017;van der Helm, Klapwijk, Stams, & van der Laan, 2009).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The higher the total score, the higher the quality of the caregiving environment. The BIC was completed by all participants, with the children using the self-report version (BIC-S; Ten Brummelaar et al, 2018); the foster carers using the version for parents (BIC-P); and the guardians using a slightly adjusted parental version (BIC-G).…”
Section: Bic (Child Foster Carer Guardian) (17)mentioning
confidence: 99%
“…The validity of the BIC-Q (version for professionals) -the basis for the development of all BIC instruments -has been examined; with the results exhibiting good construct validity (Zevulun, 2017;Zijlstra, 2012) and good reliability (Zijlstra, 2012). The construct validity and reliability of the BIC-S have also been examined, showing a moderate scale (H = .40; Rho = .86) for 11 of the 14 conditions (Ten Brummelaar et al, 2018). The reliability and validity of the BIC-P and BIC-G have not yet been examined.…”
Section: Bic (Child Foster Carer Guardian) (17)mentioning
confidence: 99%